A Novel Metal–Organic Framework Intermediated Synthesis of Heterogeneous CoS2/CoS Porous Nanosheets for Enhanced Oxygen Evolution Reaction. Issue 3 (14th January 2021) - Hu, Xiaoyue; Tan, Pengfei; Dong, Rui; Jiang, Min; Lu, Lili; Wang, Yuan; Liu, Hongqin; Liu, Yong; Xie, Jianping; Pan, Jun
Abstract : Designing and constructing transition metal sulfides (TMSs) as oxygen evolution reaction (OER) electrocatalysts has been attracting increasing attention. Interface engineering can effectively modify the active sites and promote electron transfer, resulting in improvement of electrocatalytic performance. Here, freestanding heterogeneous CoS2 /CoS nanosheets are prepared via a simple one‐step sintering process from a kind of novel hierarchical tremella‐like metal–organic framework (MOF). The formation mechanism of the unique MOF and the heterojunctions between CoS2 and CoS is analyzed. Consequently, the prepared cost‐effective OER electrocatalyst achieves satisfying electrocatalytic efficiencies with a diminutive overpotential of 269 mV at 10 mA cm −2 current density, a small Tafel slope of 52 mV dec −1, and good stability in alkaline solution comparable to RuO2 counterparts. This work opens up a new method for constructing 2D electrocatalysts containing catalytic interfaces with boosted OER performance. Abstract : Novel hierarchical tremella‐like metal–organic frameworks containing hydroxyl and organic functional groups simultaneously are synthesized as self‐sacrificing templates. The heterogeneous CoS2 /CoS porous nanosheets derived from the precursor demonstrate excellent OER performance, attributed to the unique hierarchical porous nanostructure formed by connected nanoparticles and the interfacial effects between two phases.